Morphological, structural, and thermal analysis of three part of Conocarpus cellulosic fibres - Jawaid, Mohammad; Lau, Kia Kian; Fouad, H.; Saba, N.; Alothman, Othman Y.; Hashem, Mohamed (Elsevier Editora, 2021)
Conocarpus is a buttonwood plant enriched with lignocellulosic biomass, which has high potential for various applications. In this study, different biomasses of the Conocarpus plant, such as, leaf fibers (CP–L), branches (CP–B) and trunk (CP–T), were examined collectively through characterization techniques. The chemical composition analysis showed that CP–T fibers have a higher cellulose content than CPL and CP–B fibers. Elementary analysis also detected versatile elements based on minerals such as Mg, Si, P, S, Cl, K and Ca in fiber with a high ash content. Based on the morphological analysis, the CP–T fiber with compact and striated characteristics can contribute more effectively to the reinforcement of composite materials. In addition, the particle size of the fibers increased with increasing crystallinity, which depends on the source of the fibers, being smaller in those obtained from leaves and greater in those obtained from the trunk. This finding showed that the size of the fiber is highly correlated with the stiffness of the fiber structure. In addition, all fibers regardless of their source have great thermal stability, with a high onset degradation temperature of 273.9–316.2 °C. In conclusion, Conocarpus biomass fibers, due to its advantageous properties, have a potential to be used as a bio-filler in polymer composites.